211k views
9 votes
What do i need to do

What do i need to do-example-1
User Vincent T
by
5.4k points

1 Answer

4 votes

we know that "x" and "y" are encapsulating a function in "t" terms, so then we'll do implicit differentiation on the equation.


x^2+3y=4\implies \stackrel{chain~rule}{2x\cdot \cfrac{dx}{dt}}+3\cfrac{dy}{dt}=0\implies 2x\cdot \cfrac{dx}{dt}=-3\cfrac{dy}{dt} \\\\\\ \\\stackrel{\textit{

User Dmitry Kuskov
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.